Voices from Lawrence, Kansas: Diverse Adult Learners in a University Community - Angela White; Norma Herrod (Educational Considerations, 2007)
Nestled in a neighborhood of modest bungalows, the Lawrence Adult Learning Center (LALC) is a part of the greater Lawrence High School campus. The high school annex building houses LALC, along with Native American Student Services, special education offices and personnel, and Lawrence Public Schools Nursing Services.
Keywords: programs; students; adult learning; education; community; college; diverse; culture; voices; university